Benchmarking the research performance of United Arab Emirates with gulf cooperation council countries – A bibliometric study - Ajayan, Shalini; Balasubramanian, Sreejith; Ramachandran, Sunder (Frontiers in Education, 2022)
The research performance of a country is an indicator of its scientific progress and benchmarking it with regional countries is critical to assess a country’s regional competitiveness. This study aims to assess and benchmark the research productivity of the United Arab Emirates (UAE) against other member nations of the Gulf Cooperation Council (GCC), namely with Saudi Arabia, Oman, Kuwait, Qatar, and Bahrain, who have similar macroeconomic and socio-cultural characteristics. Scopus was used as the data source to extract the research output of each of the six countries studied for the period 1995–2019. Bibliometric indicators covering both quantity and impact of research such as publication output, citation, and collaboration indicators were used to assess the research performance of UAE and other GCC countries. The findings indicate good progress in the UAE’s overall research performance during the period of study. Also, UAE’s research performance in most of the bibliometric indicators is comparable or superior to the other GCC countries. This study is the first of its kind and addresses the dearth of bibliometric studies assessing UAE’s research productivity and GCC countries in general. The findings are useful for administrators and policymakers to benchmark the performance of the UAE with other GCC countries, including its impact, growth, and trajectories. For researchers, the study indicators and methods can be replicated to assess the overall research performance of other countries.